Homeless Gods. Roman Polytheism in provincia Baetica during the Late Empire (III–IV CE) - López Gómez, José Carlos (Mohr Siebeck, 2024)
The conditions under which polytheistic ceremonies took place in Hispania during the late Roman period remain a mystery. The documentary silence is aggravated by the virtual disappearance of religious epigraphy after the rule of the Severans and the gradual abandonment of polytheistic sanctuaries. This abandonment took place during the third century, at a time when Christianity was a minority religion persecuted by the state. The causes of this collapse were the economic crisis and the development of a universalist ideology in an increasingly authoritarian empire that would ultimately undermine the model of civic religion created by Augustus. The result was that the polytheistic reality of Baetica in the fourth century had changed significantly compared to that of the second century. The construction of religious infrastructure, such as temples, was radically diminished, and cult activity was instead articulated around domestic and funerary spaces or places of collective worship still in use but lost to the archaeological record due to the lack of a physical continuity.
Keywords: Península Ibérica - Restos arqueológicos romanos; Politeísmo; Baetica; Hispania; Polytheism; Christianity; Late antiquity